2013
DOI: 10.3176/oil.2013.2s.10
|View full text |Cite
|
Sign up to set email alerts
|

High Selective Oil Shale Mining

Abstract: Several extraction technologies have been used for mining oil shale in Estonia. The quality and properties of the raw material for fuel and oil depend directly on the initial geological properties of the mineral resource. In case of kukersite oil shale in Estonia the calorific value, oil yield and limestone content vary. The paper considers possibilities for selective mining of kukersite oil shale based on tests and theoretical studies. Analyses show that selective and high selective mining extraction methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Oil shale was considered for a long time an economic hope, hence programs to operate oil shale as an energy source were launched by Scotland, Australia, France and China [1][2][3][4]. These programs eventually demonstrated that oil shale was far from being a substitute for oil because of high cost and noncompetitiveness against conventional petroleum.…”
Section: Introductionmentioning
confidence: 99%
“…Oil shale was considered for a long time an economic hope, hence programs to operate oil shale as an energy source were launched by Scotland, Australia, France and China [1][2][3][4]. These programs eventually demonstrated that oil shale was far from being a substitute for oil because of high cost and noncompetitiveness against conventional petroleum.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, selective crushing could give considerable increase in yield [4]. Most of the selective breakage and crushing technologies have already been tested in Estonia on kukersite [5,6].…”
Section: Introductionmentioning
confidence: 99%